2020
DOI: 10.1177/1455072520965017
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practice of self-medication among university students in Portugal: A cross-sectional study

Abstract: Aims: To describe the knowledge, attitudes and practices of self-medication in college students and to analyse the predicting factors for the engagement in that behaviour. Design: This is a cross-sectional study involving students ( n = 840) from a Portuguese university, selected through stratified and proportional sampling. Data were collected using a self-administered questionnaire containing, in addition to sociodemographic issues, a scale measuring knowledge about self-medication (α = .488), a scale measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 40 publications
(89 reference statements)
4
19
4
2
Order By: Relevance
“…The most common type of medication preferred for self-use was antipyretic (37.7%), multivitamins (36.4%), antihistamines (18.6%), and anti-inflammatories (17.3%). Similar findings were reported in a study conducted on students of a Portuguese University [17], and studies within Saudi Arabia [9,12]. The reasons mentioned by our students for opting for medication for self-care were minor illness (62%), previous experience (33.2%), and lack of time to attend the health care facility (23.7%).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The most common type of medication preferred for self-use was antipyretic (37.7%), multivitamins (36.4%), antihistamines (18.6%), and anti-inflammatories (17.3%). Similar findings were reported in a study conducted on students of a Portuguese University [17], and studies within Saudi Arabia [9,12]. The reasons mentioned by our students for opting for medication for self-care were minor illness (62%), previous experience (33.2%), and lack of time to attend the health care facility (23.7%).…”
Section: Discussionsupporting
confidence: 88%
“…Various national [9,10] (Mustafa and Rohra [11]; Sultan MA et al [12]; Mustafa SS et al [13]) and international (Marwa AF et al [14]; Lukovic et al [15]; Helal RM and Abou-El Wafa HS [16]; Regina FA et al [17]) studies have focused on SM behavior among college and university students, recognizing surge and widespread practice in this specific category, identifying key factors such as socio-demographic settings, lifestyle, easy accessibility and availability of medications, good knowledge, advertisement, and high level of education [18].…”
Section: Introductionmentioning
confidence: 99%
“…Stage 2: epidemiologic, behavioural and environmental diagnosis. Environmental and behavioural factors were explored in this stage, which focused on an analysis of risk behaviours for students' health (Alves et al, 2021a(Alves et al, , 2021b(Alves et al, , 2021c(Alves et al, , 2021d(Alves et al, , 2022Alves and Precioso, 2020) and identified the environmental factors on campus that might negatively affect the students' health, such as vending machines selling high-calorie food and nearby restaurants offering unbalanced meals, coffee shops and bars selling alcoholic drinks, and tobacco sales in kiosks. Health-related services on campus were also identified, including areas for physical activity and a canteen with meals carefully planned by a nutritionist.…”
Section: Intervention Developmentmentioning
confidence: 99%
“…(4) In terms of proper use of analgesics, students who have taken analgesics prescribed by doctors, those who have taken analgesics provided by family members or friends, those who have used methods other than drugs, those who have handled pain information from family members, medical professionals, those who often read the label of analgesics, and those who have taken anti-inflammatory analgesics have an obvious preference for proper use of analgesics. (5) In terms of the quality of proper use of analgesics, the students who have taken analgesics prescribed by doctors, those who have taken analgesics provided by family members/friends, those who have used healthy food/herbal medicine, and other methods other than drugs, those whose information on pain management comes from family members, medical professionals and students who often read the label of analgesics, and those who have taken antiinflammatory analgesics, their quality of using analgesics is significantly higher.…”
Section: Analysis Of the Influence Of Middle Schoolmentioning
confidence: 99%